Indium induced nanostructures on In₄Se₃(100) surface studied by scanning tunneling microscopy - Galiy, P.V.; Nenchuk, T.M.; Ciszewski, A.; Mazur, P.; Zuber, S.; Buzhuk, Ya.M. (Functional Materials, 2013)
Indium deposition leads to changes in the scanning tunneling microscopy (STM)-revealed (100) surface morphology of In₄Se₃ layered semiconductor with the formation of nanostructures, which are characterized by different dimensionality dependent on different crystal growth conditions. Preferable formation of nanodots in low and quasi one dimensional (1D) structures for the high bulk-conductivity crystals has been observed. The STM and scanning tunneling spectroscopy data enable us to consider that the dimensionality, shape and direction of the obtained indium deposition structures are induced by indium clusters available on the original, on-the-lattice-scale furrowed, ultra high vacuum (UHV) (100) cleavages of In₄Se₃ crystal due to the self-intercalation phenomenon.